Analisis Manajemen Risiko pada PT Pos Indonesia : Tinjauan Kualitatif Berbasis Studi Literatur - Kania Fitri Alyaa Nugraha; Mudji Kuswinarno (International Forum of Researchers and Lecturers, 2024)
This study aims to evaluate the risk management implemented at PT Pos Indonesia's using a qualitative approach based on literature review. Risk management is crucial for ensuring the continuity of operations, especially in the logistics sector, which faces numerous challenges. This study reviews literature on risk management in the logistics industry and evaluates its application at PT Pos Indonesia. The findings reveal that although several risk management strategies have been implemented, certain areas require improvement, particularly in operational risk mitigation and the use of technology. Recommendations include strengthening technological infrastructure and enhancing employee training on risk management awareness.